Necrotizing mastitis caused by Staphylococcus aureus in goat. Case report - Moraes, Carolina Nogueira de [UNESP]; Maia, Leandro [UNESP]; Bicudo, Luana de Cassia [UNESP]; Bicudo, Sony Dimas [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
It is reported a case of necrotizing mastitis by Staphylococcus aureus in goat whose signs were right ceiling with alteration on coloration, tenderness, consistency and bloody discharge. Supportive treatment with parenteral fluid therapy and antibiotics were performed prior to surgery to remove the affected hemigland. Additionally, postoperative topical therapy with hydrogen peroxide, tincture of iodine 2% and copper sulfate was conducted at different times. The treatment applied and the emergency care of the animal in this case were effective for improvement of the clinical case and were extremely important to maintaining the animal's life.
Keywords: mastitis; goat; copper sulfate